2017
DOI: 10.1016/j.heliyon.2017.e00328
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal symptoms in general practice: Frequency, cancer suspicions raised, and actions taken by GPs in six European countries. Cohort study with prospective registration of cancer

Abstract: BackgroundAbdominal symptoms are diagnostically challenging to general practitioners (GPs): although common, they may indicate cancer. In a prospective cohort of patients, we examined abdominal symptom frequency, initial diagnostic suspicion, and actions of GPs in response to abdominal symptoms.MethodsOver a 10-day period, 493 GPs in Norway, Denmark, Sweden, Belgium, the Netherlands, and Scotland, recorded consecutive consultations: sex, date of birth and any specified abdominal symptoms. For patients with abd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…Gastrointestinal symptoms constitute 8% to 10% of all presenting complaints reported in new primary care appointments . The majority of young adults will be diagnosed with a functional gut disorder; a minority, however, will have inflammatory bowel disease (IBD) and even fewer colorectal cancer …”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal symptoms constitute 8% to 10% of all presenting complaints reported in new primary care appointments . The majority of young adults will be diagnosed with a functional gut disorder; a minority, however, will have inflammatory bowel disease (IBD) and even fewer colorectal cancer …”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that family physicians' gut feeling, or intuition, can be highly predictive of cancer in patients with nonspecific symptoms as well as palpable tumors and abdominal symptoms and that the ability improves with the physician's age and experience. [21,26,27]. Consultancy frequency represents another criterion of interest for further study; an increased frequency of consultancies has been documented during the year prior to a diagnosis of cancer [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…4 Hence, women with abdominal symptoms consult their physicians more often than men with abdominal sympoms. 36 Furthermore, especially men with low anxiety levels take significantly longer to recognize the seriousness of their symptoms, which delays help seeking. 37 It may be hypothesized that men who hesitate to contact their physicians may participate in CRC screening, which would explain the elevated RR of being diagnosed with stage IV CRC, peaking at 1.57 for men aged 70-72 years.…”
Section: Interpretation and Other Studiesmentioning
confidence: 99%